Analysis of Agile Methods in Laravel-Based Information System Development: A Review - Wibowo, Gallen; Wardhani, Joan Anindya (International Journal of Informatics and Computation, 2026)
The rapid expansion of web-based information systems has intensified the demand for adaptive and efficient software development approaches capable of handling evolving requirements. Laravel has become a widely adopted web framework due to its modular structure and comprehensive features. However, limited synthesized evidence exists regarding which Agile methods are most commonly implemented in Laravel-based system development and the domains in which they are applied. This study conducts a Systematic Literature Review (SLR) of publications from 2022 to 2024 to examine trends in Agile adoption within Laravel projects. From 810 initial records, 32 primary studies were selected using predefined inclusion, exclusion, and quality assessment criteria. The findings reveal that Scrum is the dominant Agile method (67%), followed by Extreme Programming (XP), Rapid Application Development (RAD), and Scrumban. Productivity-oriented information systems emerge as the most prevalent application domain. Overall, the results indicate that Agile approaches particularly Scrumare highly compatible with Laravel’s iterative development model and provide practical guidance for selecting suitable methodologies in Laravel-based information system projects.